Nurses' Knowledge About Wound Management at Bhayangkara Hospital, Manado, North Sulawesi - Khair, A. Miftahul; Nasela, Sitti Johri; Intang, Sitti Nur; Djunaedi, Djunaedi; Marpaung, Sastrika Handayani (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Problems and complications that arise due to injuries, if they do not receive proper and serious treatment, can result in lifelong disability and this causes lifelong suffering for the client. The aim of the research is to determine the description of nurses' knowledge of emergency management of injured patients at Bhayangkara Hospital, Manado, North Sulawesi. This research design uses a descriptive design, a research design that is structured in such a way that researchers can obtain answers to research questions. Research design refers to the type or kind of research chosen to achieve research objectives, and acts as a tool and guide to achieve these objectives. The research results show that a person's length of work in an organization or agency is not synonymous with high productivity. People with a long period of service do not mean they have a high level of proficiency. The longer someone works, the more skilled and experienced they are in their job.